1988
DOI: 10.1007/bf00280549
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency in the attribution of parental origin of non-disjunction in trisomy 21 by both cytogenetic and molecular polymorphisms

Abstract: The precise origin of the supernumerary chromosome can be defined in the majority of trisomy 21 cases. This is achieved by evaluating the chromosome 21 short arm polymorphism and analysing restriction fragment length polymorphisms (RFLPs) of multiple chromosome 21 loci. We report a study on 37 Italian families with Down's syndrome. In 35 cases (94.6%) both the parental and the meiotic stage of non-disjunction could be established. Knowledge of the origin of the extra chromosome 21 is a pre-requisite for invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Through the use of quinacrine fluorescence variants [Juberg and Mowrey, 19831, quinacrine and NOR variants [Mikkelsen et al, 1980;Jackson-Cook et al, 19851 and fluorescent R-banding [Verma et al, 19861, cytogenetic heteromorphisms have been used for the identification of the parental origin of the extra chromosome 21 in Down syndrome. Restriction fragment length polymorphisms have been used more recently to assign the parental origin and meiotic stage of the nondisjunctional error resulting in trisomy 21 [Davies et al, 1984;Stewart et al, 1985;Hamers et al, 1987;Stewart et al, 1988;Dagna Bricarelli et al, 1988;Rudd et al, 1988;Galt et al, 1989;Antonarakis et al, 19911. Additionally, RFLPs have become helpful for studying nondisjunction, especially in cases where the cytogenetic markers were uninformative or ambiguous [Stewart et al, 1988;Millington Ward and Pearson, 1988;Antonarakis et al, 19913.…”
Section: Discussionmentioning
confidence: 99%
“…Through the use of quinacrine fluorescence variants [Juberg and Mowrey, 19831, quinacrine and NOR variants [Mikkelsen et al, 1980;Jackson-Cook et al, 19851 and fluorescent R-banding [Verma et al, 19861, cytogenetic heteromorphisms have been used for the identification of the parental origin of the extra chromosome 21 in Down syndrome. Restriction fragment length polymorphisms have been used more recently to assign the parental origin and meiotic stage of the nondisjunctional error resulting in trisomy 21 [Davies et al, 1984;Stewart et al, 1985;Hamers et al, 1987;Stewart et al, 1988;Dagna Bricarelli et al, 1988;Rudd et al, 1988;Galt et al, 1989;Antonarakis et al, 19911. Additionally, RFLPs have become helpful for studying nondisjunction, especially in cases where the cytogenetic markers were uninformative or ambiguous [Stewart et al, 1988;Millington Ward and Pearson, 1988;Antonarakis et al, 19913.…”
Section: Discussionmentioning
confidence: 99%
“…The assignment of the haplotypes was possible in the majority of cases for groups A and B, combining both the cytogenetic and -molecular data of the father (F), mother (M), and children (DS or NC) (8). The criteria used are exemplified in Fig.…”
mentioning
confidence: 99%
“…2b) was helpful in determining the linkage phase. A few recombinational events preceding the NDJs at meiosis I and II were recognized by combining both the cytogenetic and the molecular analysis (8 …”
mentioning
confidence: 99%
“…However, we have shown that a large proportion of parental origins of de novo rearrangements can be determined using combined QFQ/NOR heteromorphism data (75%). Restriction fragment length polymorphisms have been used by other investigators to assign the parental origin and meiotic stage of the nondisjunctional error resulting in trisomy 21 (Davies et al 1984;Stewart et al 1985Stewart et al , 1988Hamers et al 1987;Dagna Bricarelli et al 1988;Rudd et al 1988;Galt et al 1989;Meijer et al 1989). Using a sufficient number of DNA markers spanning the length of the chromosome, it is theoretically possible to assign the parental origin of nondisjunction in virtually all cases of trisomy 21 Chakravarti 1989).…”
Section: Discussionmentioning
confidence: 96%